Country Paper :1. Improvement of community wellbeing in Malaysia ; 2. Strategic planning of town/city – efficient public transport lead to better environment and living environment in Malaysia - Mohd Nawawi, Norwina; Shankar, Thirilogachandran (2012)

(untitled)
A country paper on Malaysia depicting the improvement and measures taken and planned for the community wellbeing as well as strategic planning for efficient transport system. The presentation introduces the fundamental principles of corporate social responsibility of Malaysia through Malaysian's own quality of life index that follows with the various plans,events and organisation addressing the subject in toto. The paper highlight areas where architects could contribute and ends with various achievements and mileage the actions had achieve and still looking forward to through establishment on chapter of Architecture for Humanity.